2019
DOI: 10.1002/ange.201905407
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Catalysis by Cooperative Vibrational Strong Coupling of Reactant and Solvent Molecules

Abstract: Here,w er eport the catalytic effect of vibrational strong coupling (VSC) on the solvolysis of para-nitrophenyl acetate (PNPA), which increases the reaction rate by an order of magnitude.T his is observed when the microfluidic Fabry-Perot cavity in whichthe VSC is generated is tuned to the C=O vibrational stretching mode of both the reactant and solvent molecules.T hermodynamic experiments confirm the catalytic nature of VSC in the system. The change in the reaction rate follows an exponential relation with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 24 publications
3
73
1
Order By: Relevance
“…For example, mode selective chemistry experiments have shown that TS control of the reaction can be modulated by anisotropic forces either to enhance or suppress a particular reaction path [38]. In other words, the role of strong coupling could be more important in determining the position and structure of the TS as shown in recent experimental [6,8] and theoretical studies [23,24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, mode selective chemistry experiments have shown that TS control of the reaction can be modulated by anisotropic forces either to enhance or suppress a particular reaction path [38]. In other words, the role of strong coupling could be more important in determining the position and structure of the TS as shown in recent experimental [6,8] and theoretical studies [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Light-matter strong coupling is evolving as a physical tool for chemists to control chemical reactivity [1][2][3][4][5][6][7][8][9][10]. This was triggered by the modified spiropyran-merocyanine photoisomerisation dynamics under the electronic strong coupling (ESC) [2] and further fuelled by the development of vibrational strong coupling (VSC), where the vibrational mode of a molecule is strongly coupled [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations